Portfolio balance effects of the SNB's bond purchase program - Andreas Kettemann; Signe Krogstrup (University of Zurich, Department of Economics, 2013)
This paper carries out an empirical investigation of the impact on bond spreads of the announcement, purchases and exit from the SNB's bond purchase program in 2009-2010. We find evidence in favor of a narrowing yield spread of covered bonds as a result of the program. The effect materialized in the days following the announcement of the SNB's intention to buy bonds issued by private sector borrowers, as markets learned that the SNB was buying covered bonds. The specification of the bond spreads used allows us to identify this effect as a discounted portfolio balance effect of the expected purchases, as distinct from policy signalling. In contrast, we find no evidence of a further effect of the actual purchases and subsequent sales on bond spreads.
Keywords: E5; G1; 330; portfolio balance; credit spread; corporate spread; unconventional monetary policy; central bank asset purchases; credit easing; zero lower bound; Öffentliche Anleihe; Geldpolitik; Kreditpolitik; Bankrechnungslegung; Zentralbank; Schweiz